Kecemasan dan Konsentrasi Pada Atlet Panahan - Jannah, Miftakhul (Jurnal Psikologi Teori dan Terapan, 2017)
The purpose of this study to determine the relationship between anxiety and concentration in archery athletes. The subject of this study were 14 archery athletes Surabaya. Data collecting use Sports Anxiety Scale to measure anxiety and Grid Concentration Exercise to measure the concentration level of research subjects. Data Analysis is using product moment correlation. The result show the correlation coefficient value of -0.779 with significance level of 0.001 <0.05. Based on these results, it can be said that there is a relationship between anxiety and the concentration of the archery athlete in which the direction of the relationship is negative. It mean, any increasing anxiety will be accompanied by a decreasing archery athletes’ concentration. Vice versa, decreasing anxiety levels will be followed by an increasing concentration of archery athletes. This indicates anxiety is an internal distractor that affects the archery athletes’ concentration. Athletes who have high anxiety, means the stimulus attracted the athlete's attention to a lot. Consequently, athletes fail to conduct selective attention by sorting the stimuli received by the senses so that the athlete's concentration easily becomes split.Abstrak: Tujuan penelitian ini untuk mengetahui hubungan antara kecemasan dan konsentrasi pada atlet panahan. Sejumlah 14 orang atlet panahan Surabaya yang menjadi subjek penelitian. Pengukuran variabel-variabel penelitian dilakukan dengan instrumen berupa Skala Kecemasan Olahraga untuk mengukur kecemasan dan Grid Concentration Exercise untuk mengukur tingkat konsentrasi subjek penelitian. Analisis data penelitian dilakukan menggunakan korelasi product moment. Hasil analisis data menunjukkan nilai koefisien korelasi sebesar -0.779 dengan taraf signifikansi sebesar 0.001 < 0.05. Berdasarkan hasil tersebut, dapat dikatakan bahwa ada hubungan antara kecemasan dan konsentrasi atlet panahan di mana arah hubungan tersebut adalah negatif. Maknanya, setiap peningkatan kecemasan akan diiringi dengan penurunan tingkat konsentrasi atlet panahan. Begitu pula sebaliknya, penurunan tingkat kecemasan akan diikuti dengan peningkatan konsentrasi atlet panahan. Hal ini menunjukkan kecemasan merupakan distraktor internal yang berpengaruh terhadap konsentrasi atlet. Atlet yang memiliki kecemasan tinggi, berarti stimulus-stimulus yang menarik atensi atlet menjadi banyak. Imbasnya, atlet gagal melakukan atensi selektif dengan menyortir stimulus-stimulus yang diterima inderanya sehingga konsentrasi atlet mudah menjadi terpecah.